The Role of Parenting Patterns in Children's Emotional Development - Samsidar, Samsidar (Psikologiya Journal, 2025)
Children's emotional development is an important foundation in the formation of personality, social behavior, and mental health in the future. Parenting patterns are one of the crucial factors that influence how children learn to recognize, manage, and express their emotions. This article aims to explore the relationship between various types of parenting patterns (authoritarian, authoritative, permissive, and neglectful) with the emotional development of children from early childhood to early adolescence. This study used a qualitative approach with in-depth interview techniques with ten families from different socio-economic backgrounds. The results showed that authoritative parenting positively contributed to children's emotional regulation, while authoritarian and neglectful parenting tended to correlate with increased anxiety, aggressiveness, and difficulties in social adaptation. In addition, it was found that cultural context and relational factors (such as emotional communication between parents and children) greatly influenced the effectiveness of parenting patterns in supporting children's emotional development. This study suggests the importance of positive parenting training for parents as a preventive measure against disorders in children's emotional development.